Virtual Sensors Design for Nonlinear Dynamic Systems - Alexey Zhirabok; Alexander Zuev; Kim Chung Il (International Journal of Robotics and Control Systems, 2023)
The objective of the paper is virtual sensors design, estimating prescribed components of the systems state vector to solve the tasks of fault diagnosis in nonlinear systems. To solve the problem, the method called logic-dynamic approach is used, which allows to solve the problem for systems with non-smooth nonlinearities subjected to external disturbance by methods of linear algebra. According to this method, the problem is solved in three steps: at the first step, the nonlinear term is removed from the system, and the linear model invariant with respect to the disturbance is designed; at the second step, a possibility to take into account the nonlinear term and to estimate the given variable is checked; finally, the transformed nonlinear term is added to the linear model. The relations allowing to design virtual sensor of minimal dimension estimating prescribed component of the state vector of the system are obtained. The main contribution of the present paper is that a procedure to design virtual sensors of minimal dimension for nonlinear systems estimating prescribed components of the state vector is developed. This allows to reduce complexity of the virtual sensors in comparison with known papers where such sensors of full dimension are constructed. Besides, the limitations imposed on the initial system are relaxed that allow to extend a class of systems for which the virtual sensors can be constructed.